Caramella Enterprise - Md Shah, Murny; Kussenan, Farahah; Mahadi, Nur Hidayu; Rasiman, Nur Hasanah; Ahmad, Siti Nur Azlina (2012)
Caramella Enterprise is a partnership-based food product business located near One Segamat Shopping Centre, focusing on serving the local community in the Segamat area. The company provides a list of snack products, specifically specializing in chocolate, candy, and peanuts. The business is led by six upper managers: the Chief Executive Officer, Marketing Manager, Financial Manager, Administrative Manager, and two Operational Managers, all of whom contribute capital to run the enterprise. Caramella Enterprise is committed to offering high-quality food, a comfortable environment, reasonable prices, and friendly customer services. The shop also provides booking services for customers and gives consideration to any additional service requests or compliments to ensure satisfaction. The primary goal is to conduct efficient and effective business transactions by continuously striving to capture customer interest and fulfill their satisfaction, thereby ensuring the smooth operation and achievement of the company's objectives.